Ensuring equity with pre-clinical planning for chlamydia vaccines - Amanda L. Collar; Tegan N. Clarke; Andzoa N. Jamus; Kathryn M. Frietze (npj Vaccines, 2023)
Abstract Chlamydia trachomatis (Ct) remains the most common bacterial sexually transmitted pathogen worldwide, causing significant morbidity particularly among women, including pelvic inflammatory disease, ectopic pregnancy, and infertility. Several vaccines are advancing through pre-clinical and clinical development, and it is likely that one or more vaccines will progress into human efficacy trials soon. In this Perspective, we present a case for considering the challenges of Ct vaccine development through a lens of equity and justice. These challenges include the need to protect against multiple serovars, in both females and males, at multiple anatomic sites, and in resource poor areas of the world. We propose that early consideration of vaccine implementation by conducting community-engaged research will ensure that a scientifically sound chlamydia vaccine promotes equity, justice, and shared-gendered responsibility for STI prevention.